An unusual complication of Mitek suture anchor use in primary treatment of flexor digitorum profundus tendon laceration: a case report - Giannikas, Dimitrios (BioMed Central, 2009)
INTRODUCTION: A case of an osteolysis by Mitek anchor-suture is presented. CASE PRESENTATION: A case of index finger's flexor digitorum profundus tendon primary reconstruction with the use of Mitek anchor is presented here. Within a 14 month period, Mitek suture anchor caused local foreign body reaction with osteolysis and ulceration of the palmar skin of the finger while on the other hand tendon's healing was successfully completed. CONCLUSION: Mitek anchor-sutures can cause an aseptic inflammatory reaction which represents a typical biologic response to a foreign body. Concomitant osteolysis can drive to loosening and migration of the implant.